Physical Parameters Influence The Microbial Quality Of Indoor Air In Research Laboratories: A Report From Malaysia - Kuilan Yogeswaran; Liyana Azmi; Subha Bhassu; Hafizah N. Isa; Muhamad Afiq Aziz (Elsevier, 2024)
Indexed by WOS/ Scopus